A model with endogenous programme participation: evaluating the tax credit in France - Hans G. Bloemen; Elena G. F. Stancanelli (Institute for the Study of Labor (IZA), 2007)
This paper provides new estimates of the impact of the French tax credit on the employment outcomes of women. We model simultaneously the employment probability and the determinants of programme eligibility. We improve on earlier studies in this field that, using a single evaluation equation framework, predicted ex-ante programme eligibility. Within this framework, we also allow for hours responses. The data for the analysis are drawn from the French labour force surveys of years 1999 to 2002. We find no significant impact of the tax credit on either employment or hours of French women.
urn:nbn:de:101:1-20080422132
Keywords: 330; Einkommensteuerpolitik; Steuerbegünstigung; Steuerwirkung; Frauenerwerbstätigkeit; Arbeitsangebot; Beschäftigungseffekt; Frankreich